Integrated Curriculum: Optimizing the Multiple Intelligences of Senior High School Students in Indonesia - Falaqi Muhamad Rizal; Yusuf Athayya Einosar; Husein, Muhammad Ghafiq; Susanto, Nabil Huga Arundaya; Nugroho, Arsya Sakha; Firdausy, Alif, Dzulfiqar Achmad; Abdurrahim, Istna Hasan (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: With the goal of maximizing students’ Multiple Intelligences (MI), this study aims to describe curricular integration in the senior high school context and explores how it is applied as the main curriculum strategy in senior high schools. Methodology: An international boarding school is the context of the case study methodology. Using a Triangulation method technique, direct observation, interviews, and documentation are all part of the data collection process. Reducing, organizing, and extrapolating conclusions from data with content analysis was performed. Findings: According to the research findings, the